IMPLEMENTATION OF WORKERS' LEGAL RELATIONS IN OUTSOURCED COMPANIES AND PROVISIONS FOR TERMINATION OF EMPLOYMENT AFTER THE ENACTMENT OF LAW NO 6 OF 2023 CONCERNING JOB CREATION - Sugianto, Putu Erman; Bethlen, Andrew; Saragi, Paltiada (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2024)
Outsourcing in Indonesia has its advantages and disadvantages. It can create jobs and help reduce unemployment, but it also often creates problems between workers and companies. Every individual needs a job to earn a decent living, in accordance with the principles of the state. The government should ensure the welfare of its citizens by providing employment opportunities, as stipulated in the law. However, in practice, workers often lack adequate protection, especially with types of employment contracts such as non-permanent contracts that are favoured by employers because they reduce wage costs. Contracts such as non-permanent contracts can make workers feel anxious about the stability of their jobs and wages. Government intervention is considered essential to protect workers' rights. Law No. 13 Year 2003 regulates non-permanent contracts, and although it was revised by the Omnibus Law and Law No. 6 Year 2023, many people felt there were no significant changes. There is debate over the article that allows outsourcing of some jobs. In some cases, such as what happened at PT BM Tbk, there were violations of the law's provisions regarding PKWT, which made the employment relationship unclear. This research aims to understand more about the legal relationship of workers in outsourcing companies and the implications of Law No. 6 of 2023, as well as its impact on termination of employment. Therefore, this study aims to discuss the implementation of the legal relationship of workers in outsourcing companies after the enactment of Law No. 6 of 2023 as well as the termination of employment of workers in these companies, in comparison with Decision No. 524 K/Pdt.Sus-Phi/2022.This research uses the normative legal method, also known as doctrinal legal research, to understand the law as rules in legislation. The method is descriptive analytical, explaining current conditions based on facts. The approach used includes the analysis of relevant laws. The data used is secondary data from the literature, including primary, secondary, and tertiary legal materials, collected through documentation. Data analysis was conducted in a qualitative descriptive manner to answer the research problem. The research shows that the legal relationship between workers in outsourcing companies and layoffs after Law No. 6 of 2023 still does not provide legal certainty and justice. This is due to the uncertainty in the law and the unfairness of workers' positions. Three factors that impede justice are the lack of application of the principle of judicial independence, the vacuum of norms, and the utilisation of legal weaknesses by employers. The author suggests revising the law by involving the community and reminding outsourcing companies to follow the law for the sake of legal certainty and justice for workers.